PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 77 PEKANBARU - Heroza Firdaus; Eddy Noviana; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievement of social fourth graderes studies still low with an average value of 65,31 and minimum completeness criteria (KKM) social studies is 75. Between students, amounting to 32 people only 13 students who achieve classical KKM with 40,62%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of social studies class IV at SD Negeri 77 Pekanbaru with implementation cooperative learning model type jigsaw. Formulation of the problem : Is the implementation of cooperative learning model type jigsaw can improve students achievement of social studies class IV at SD Negeri 77 Pekanbaru? The research was conducted on August 15 to September 26, 2015 by 3 cycles. Subjects were students of SD Negeri 77 Pekanbaru, totaling 32 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 65,31. In the first cycle improve an average of 67,81 with increase big as 3,82% and an improve in the second cycle with an average of 76,40 with increase big as 16,98%. and an improve in the third cycle with an average of 83,12 with increase big as 27,26%. Activities of the teacher in the learning process in cycle I first meeting improve to 54,16% and the second meeting improve to 62,5%. Cycle II first meeting improve to 70,83 and the second meeting improve to 79,17%. Cycle III first meeting improve to 87,5 and the second meeting improve 91,66%. Results of data analysis of students activities in the first cycle with the first meeting of an average of 50% and a second meeting improve to 62,5%. Second cycle first meeting improve to 70,83% and the second meeting improve to 79,16%. Third cycle III at the first meeting of 87,5, and the second meeting improve to 91,66%. Results in the class IV at SD Negeri 77 Pekanbaru that the implementation of cooperative learning model of Jigsaw can improve the student achievement of social studiesat fourth graderes SD Negeri 77 Pekanbaru.Key Words: Mode cooperative Jigsaw, the result of studying social sciences